2022
DOI: 10.1029/2022jd037617
|View full text |Cite
|
Sign up to set email alerts
|

Using Neural Networks to Predict Hurricane Storm Surge and to Assess the Sensitivity of Surge to Storm Characteristics

Abstract: Hurricane storm surge represents a significant threat to coastal communities around the world. Here, we use artificial neural network (ANN) models to predict storm surge levels using hurricane characteristics along the US Gulf and East Coasts. The ANN models are trained with storm surge levels from a hydrodynamic model and physical characteristics of synthetic hurricanes which are downscaled from National Centers for Environmental Prediction (NCEP) reanalysis using a statistical‐deterministic hurricane model. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 47 publications
0
13
1
Order By: Relevance
“…This may be a result of the rain rates levels being more directly influenced by changes in storm intensity change, as in the TCRM. Additionally, storm surge is also significantly influenced by other factors unrelated to intensity, including the shape of the coastline, depth of the continental shelf and storm translation speed (Lockwood, Lin, et al., 2022).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This may be a result of the rain rates levels being more directly influenced by changes in storm intensity change, as in the TCRM. Additionally, storm surge is also significantly influenced by other factors unrelated to intensity, including the shape of the coastline, depth of the continental shelf and storm translation speed (Lockwood, Lin, et al., 2022).…”
Section: Resultsmentioning
confidence: 99%
“…We note that in this modeling set‐up with the outer size of the TCs derived from an empirical lognormal distribution (Chavas et al., 2015), wind intensity has an inverse correlation with Rmax. However, storm track including storm forward speed, can affect also storm surge levels, but its effect are complex depending on coastal geometry (Lockwood, Lin, et al., 2022). We have not examined if the track features of RI storms are different from those of non‐RI storms.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research indicates that wind speed, air pressure, wind direction, and proximity are crucial for predicting storm surges using machine learning techniques (Ian et al, 2022;Tiggeloven et al, 2021). Moreover, to provide a more holistic understanding of storm surges, additional studies have integrated morphological characteristics, oceanic conditions, and temporal patterns into their analyses (Huang, 2022;Li et al, 2023;Lockwood et al, 2022;Rajabi-Kiasari et al, 2023). These aspects help to elucidate the dynamics of storm surges, including wind force, oceanic movements, and landform interactions.…”
Section: Discussionmentioning
confidence: 99%
“…Zhang and Jiang employed four optimization algorithms (including genetic algorithm, particle swarm optimization, beetle antennae search, and beetle swarm optimization) to optimize Back Propagation Neural Networks, proposing four optimized BPNN for predicting storm surge disaster risk [35]. Lockwood et al found that ANN models trained on synthetic datasets could predict storm surge levels along the eastern United States and the Gulf of Mexico, providing scientific support for relevant departments to take preventative and disaster mitigation measures [36].…”
Section: Recent Studies Using Artificial Intelligence-based Techniquesmentioning
confidence: 99%